The hidden curriculum. - Rodriguez RG; Mai D; Rodriguez, Rechell G; Mai, Derek (Military Medicine, 2012)
The Uniformed Services University of the Health Sciences Internal Medicine Third Year Clerkship Program recently instituted an academic exercise to be completed by medical students during the first 6 weeks of their 12 weeks of Internal Medicine. The academic exercise involves reflecting on professional values through art and being exposed to the hidden curriculum of professionalism. Students are instructed at the beginning of their clerkship to observe the professional activities of their teachers, peers, ancillary staff, and of themselves. Students are provided a selection of art pieces to choose from. They select one which best exemplifies the professional activity they observed and are then to write a structured, reflective article.